2019
DOI: 10.1088/1755-1315/308/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Production of indole acetic acid by Enterobacter cloacea H3 isolated from Mungbean (Vigna radiata) and its potential supporting the growth of soybean seedling

Abstract: Many plant-associated bacteria synthesize the phytohormone indole acetic acid (IAA). Three bacterial isolates (H1, H2 and H3) were isolated from root nodules of Mungbean (Vigna radiata) and tested for their productivity of indole acetic acid by spectrophotometric method. Isolate H3 showed the highest IAA production (12.28 μg/ml) in culture medium supplemented with L-Tryptophan. Based on 16S rRNA gene analysis, isolate H3 was identified as Enterobacter cloacae. The cultures condition optimized for maximum IAA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Results of their study showed that E. cloacae (B1) effectively increased growth characteristics including plant height, fresh weight, dry weight, flag leaf area, and physiological characteristics including chlorophyll pigments content and yield characteristics such as spike length, spikelets number, grains number/spike, 1000 kernels weight, spike weight, biological weight and grains weight, in comparison with control treatment. Opposite to this, the results of Widowati et al [23] showed that the germination percentage and rate of soybeans were not significantly different between controls and Enterobacter cloacea isolate H3 treated samples.…”
Section: Introductionmentioning
confidence: 84%
“…Results of their study showed that E. cloacae (B1) effectively increased growth characteristics including plant height, fresh weight, dry weight, flag leaf area, and physiological characteristics including chlorophyll pigments content and yield characteristics such as spike length, spikelets number, grains number/spike, 1000 kernels weight, spike weight, biological weight and grains weight, in comparison with control treatment. Opposite to this, the results of Widowati et al [23] showed that the germination percentage and rate of soybeans were not significantly different between controls and Enterobacter cloacea isolate H3 treated samples.…”
Section: Introductionmentioning
confidence: 84%
“…Only one of the 10 Pseudomonas isolates from tomato rhizosphere, BF2P5-1, produced IAA. IAA production by PGPR varies among species and strains and is influenced by culture conditions, growth stage, and substrate availability [45].…”
Section: Discussionmentioning
confidence: 99%
“…The isolate Enterobacter cloacae produced 2.443 ìg/ml of IAA 35 . The isolate Enterobacter cloacae H3 produced 12.28 ìg/ml IAA after 5 th day of incubation 13 .…”
Section: Indole Acetic Acid (Iaa) Productionmentioning
confidence: 99%
“…Numerous Enterobacter spp. having the potential to produce indole acetic acid (IAA) such as E. cloacae H3, E. cloacae NII-0931, E. cloacae MSR1, E. cloacae UW 5, E. asburiae, E. cancerogenus 13 .…”
mentioning
confidence: 99%